2023
DOI: 10.1186/s40001-023-01088-5
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus and its associated factors in Ethiopia: a systematic review and meta-analysis

Abstract: Background In Ethiopia, gestational diabetes mellitus (GDM) is a significant public health issue and a risk to maternal and child health. Understanding the prevalence and factors of GDM in Ethiopia may also help determine the best interventions. Therefore, we tried to review gestational diabetes and its factors in Ethiopia.AQ: Please check and confirm the edit made to the article title.yes i have checked and confirm Methods The Preferred Reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
3
2
0
Order By: Relevance
“…Of the studies, overweight or obesity, advanced maternal age, family history of diabetes and having a previous history of gestational diabetes mellitus were significant predictors of gestational diabetes. These findings are consistent with Beyene et al [10], a systematic review in Ethiopia, who reported that high body mass index, family history of diabetes and previous history of GDM were significantly associated with experiencing gestational diabetes. Similarly, a systematic review by Kiani et al [62] in Iran found excess weight and obesity, older maternal age, family history of diabetes and history of gestational diabetes as predictors of gestational diabetes [62].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Of the studies, overweight or obesity, advanced maternal age, family history of diabetes and having a previous history of gestational diabetes mellitus were significant predictors of gestational diabetes. These findings are consistent with Beyene et al [10], a systematic review in Ethiopia, who reported that high body mass index, family history of diabetes and previous history of GDM were significantly associated with experiencing gestational diabetes. Similarly, a systematic review by Kiani et al [62] in Iran found excess weight and obesity, older maternal age, family history of diabetes and history of gestational diabetes as predictors of gestational diabetes [62].…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, it is similar to the prevalence reported in sub-Saharan Africa (2%-6%) by Mwanri et al [9] and in Europe (5.4%) as per a meta-analysis by Eades et al [57]. However, the GDM prevalence observed in this review is notably lower than that found in a systematic review in Ethiopia conducted by Beyene et al [10], who reported a pooled prevalence of 12.04%. It is also lower than the prevalence recorded in the United States from the National Health and Nutrition Examination Surveys between 2007 and 2014 (7.6%) [58].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…20 In Ethiopia, the pooled prevalence of GDM is 12.04% (95% CI (8.17% to 15.90%)). 21 In this regard, it has been acknowledged that an inadequate level of GDM knowledge among pregnant women has contributed significantly to the increase in cases in this population. Despite this evidence, no study has been conducted in Ethiopia to investigate pregnant women's knowledge of GDM.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%